Phosphatidylcholine biosynthesis in Xanthomonas campestris via a yeast‐like acylation pathway. Issue 4 (7th January 2014) - Moser, Roman; Aktas, Meriyem; Narberhaus, Franz
Summary Two principal phosphatidylcholine (PC) biosynthesis pathways are known in bacteria. S‐adenosylmethionine (SAM)‐dependent phospholipid N‐methyltransferases (Pmt) catalyse the threefold N‐methylation of phosphatidylethanolamine (PE) to PC. In an alternative pathway, the PC synthase (Pcs) condenses CDP‐diacylglycerol and choline to produce PC. In this study, we investigated phospholipid biosynthesis in the plant pathogen Xanthomonas campestris that was found to contain significant amounts of monomethylated PE (MMPE) and small amounts of PC. We identified a Pmt enzyme that produces MMPE without methylating it further to PC. Surprisingly, PC production was independent of [14C]‐SAM and [14C]‐choline excluding canonical Pmt or Pcs pathways. Feeding experiments with various choline derivatives revealed a novel, yeast‐like PC synthesis route in Xanthomonas, in which two acyl side‐chains are added to a glycerophosphocholine (GPC) backbone. Two out of 12 tested acyltransferases from Xanthomonas were able to catalyse the second acylation step from lyso‐PC to PC. This first description of GPC‐dependent PC production in bacteria illustrates an unexpected diversity of PC biosynthesis pathways.